Secondary storage reservoir: a potential option for rainwater harvesting in irrigated command for improved irrigation and agricultural performance - Mishra, Atmaram; Ghosh, S.; Mohanty, R.K.; Brahmanand, P.S.; Verma, H.C. (Diva Enterprises Private Limited, 2014)
Present study recommends an option to overcome the limited water availability in surface irrigation system through provision of secondary reservoirs in the command. The harvested water can be utilized for irrigation in the dry season, short duration fish culture, etc. Approximately 10% of the command area is required for the secondary reservoir with assumption of 50% capacity of the main reservoir will be available for irrigating dry season crops. The demonstration of use of water from the secondary reservoir in addition to the water from main reservoir has resulted in substantial crop and fish yield. The gross and net returns from various cropping patterns considered using irrigation water from main reservoir (MR) and from main and secondary reservoir (MR+SR). Among the cropping patterns considered, rice-tomato cropping pattern resulted in highest net return of INR 29,457/ha followed by rice-brinjal cropping pattern (INR 22,430/ha) with benefit cost ratio of 2.07 and 1.79, respectively. Highest benefit-cost ratio of 2.09 was obtained for rice-sunflower cropping system due to relatively lower cost of cultivation of sunflower. The highest incremental value of net returns of 3710 `/ha was obtained with rice-tomato cropping system. The low input-based scientific fish culture in the secondary reservoir has enhanced the fish yield by three fold over traditional practice increasing the gross return from the system. The economic analysis also revealed that the intervention is economically viable.